PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PPKN - BAMBANG SUHARTO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Based on data in the field, the motivation and learning outcomes of PPKn students at SMP Negeri 2 Peterongan class IX-F are still relatively low/there are data, this can be seen from the concentration of students in participating in Civics learning that is less enthusiastic, students easily forget new concepts accepted, many students do not pay attention to the teacher's explanation because the teacher's methods have been conventional, the learning strategies carried out are teacher-centered so that students tend to be passive and feel bored. The purpose of this study was to improve the learning outcomes of class IX-F students at SMP Negeri 2 Peterongan by implementing Discovery Learning. This research is a Classroom Action Research (CAR) conducted in 2 cycles. Each cycle carried out 2 meetings and after the cycle 1 was completed, the learning outcomes and reflection tests were carried out which were used for follow-up in cycle 2. And after the second cycle the research results were analyzed data. The results of the study show that the application of the Discovery Learning Learning Model can increase teacher activities, student activities and PPKn learning outcomes for class IX-F students of SMP Negeri 2 Peterongan in the 2021/2022 academic year. The results of observations in cycle 1 show that the percentage of teacher activity reaches 80%, the percentage of student activity reaches 67%, and the acquisition of student learning outcomes is 74% of students who complete. In cycle 2, the percentage acquisition of the implementation of teacher activities reached 86%, student activity was 84%, and the acquisition of student learning outcomes was 87% of students who completed In cycle 1 there were still 8 students whose learning outcomes were below the KKM (not completed). ), while in cycle 2 there were 4 students who did not complete. The activeness of students in asking and discussing has also increased. Suggestions from research results are expected for teachers to apply Discovery Learning in the learning process. In the application of Discovery Learning, it is necessary to pay attention to the teacher's ability to motivate students and provide a stimulus so that students are provoked to ask questions in learning. ABSTRAKBerdasarkan data di lapangan, motivasi dan hasil belajar PPKn peserta didik SMP Negeri 2 Peterongan kelas IX-F masih tergolong rendah/ada data, hal ini dapat terlihat dari konsentrasi peserta didik dalam mengikuti pembelajaran PPKn kurang semangat, peserta didik mudah sekali melupakan konsep yang baru diterima, banyak peserta didik yang tidak memperhatikan penjelasan guru dikarenakan metode guru selama ini konvensional, strategi pembelajaran yang dilakukan berpusat pada guru sehingga peserta didik cenderung pasif dan merasa bosan. Tujuan penelitian ini adalah untuk meningkatkan hasil belajar peserta didik kelas IX-F di SMP Negeri 2 Peterongan dengan penerapan Discovery Learning. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilakukan sebanyak 2 siklus. Setiap siklus dilaksanakan 2 pertemuan dan setelah siklus 1 selesai dilaksanakan tes hasil belajar dan refleksi yang digunakan untuk tindak lanjut pada siklus 2. Dan setelah dilaksanakan siklus 2 hasil penelitian dilakukan análisis data. Hasil penelitian bahwa Penerapan Model Pembelajaran Discovery Learning dapat meningkatkan aktivitas guru, aktivitas peserta didik dan hasil belajar PPKn peserta didik kelas IX-F SMP Negeri 2 Peterongan tahun pelajaran 2021/2022. Hasil observasi pada siklus 1 menunjukkan persentase aktivitas guru mencapai 80%, persentase aktivitas peserta didik mencapai 67%, dan perolehan hasil belajar peserta didik adalah 74% peserta didik yang tuntas. Pada siklus 2, perolehan persentase keterlaksanaan aktivitas guru mencapai 86%, aktivitas peserta didik sebesar 84%, dan perolehan hasil belajar peserta didik adalah 87% peserta didik yang tuntas Pada siklus 1 masih terdapat 8 peserta didik yang hasil belajarnya di bawah KKM (tidak tuntas), sedangkan pada siklus 2 terdapat 4 peserta didik yang tidak tuntas. Keaktifan peserta didik dalam bertanya dan berdiskusi juga mengalami peningkatan. Saran hasil penelitian adalah diharapkan kepada para guru untuk menerapkan Discovery Learning dalam proses pembelajaran. Dalam penerapan Discovery Learning , perlu diperhatikan tentang kemampuan guru dalam memotivasi peserta didik dan memberikan stimulus sehingga peserta didik terpancing untuk mengajukan pertanyaan dalam pembelajaran